Effect Of Deposition Duration And Concentration Of Chemical Bath In The Formation Of Zinc Selenide Thin Films (Bangladesh Journal of Physics, 2025)
Zinc selenide (ZnSe) thin films were produced onto glass substrates using chemical bath deposition technique varying the concentration of the Se source and the deposition duration. It is observed that, the duration of deposition and concentration of Se source emerged as significant factors influencing the surface morphology of the films. When films are deposited for different duration keeping the concentration of Se source constant in the chemical bath, 40 min of deposition is found to be optimum duration for deposition. However, when concentration varied, 1.0 M found to be suitable for film formation of desired structure. The elements present in the films confirmed the purity of the film as observed from EDX study. In terms of optical properties, the observed ZnSe thin films displayed varying optical band gap energies in the range of 2.50 to 3.80 eV, which remain almost independent on duration of deposition when concentration of Se source kept constant, however depend on the concentration of the Se source though duration of deposition was kept constant. The result of this study suggests the suitability of this films in optoelectronic devices.Bangladesh Journal of Physics, 28(1), 11-24, June 2021